Secular trends and smoke-free policy development in rural Kentucky - Fallin, Amanda (Oxford University Press, 2011)
Secondhand smoke (SHS) exposure causes cardiovascular disease, lung cancer and pulmonary disorders. Smoke-free policies are the most effective way to prevent exposure to SHS. A 5-year community-based randomized control trial (RCT) is in progress to assess factors associated with smoke-free policy development in rural communities. Considering secular trends is critical when conducting community-based RCTs as they may threaten the internal validity of the study. For the purposes of this paper, secular trends are defined as patterns or recurring events that are not directly related to smoke-free policy but have the potential to influence policy development. There are no established protocols to monitor secular trends in the study of smoke-free policy in rural communities. The purpose of this paper is to (i) describe the development of a protocol to identify and monitor secular trends that may threaten the internal validity of a community-based RCT to promote smoke-free policy development and (ii) describe secular trends identified in the first 2 years of the RCT. The sample includes 854 secular events captured from media outlets covering the 40 study counties over the first 2 years of the RCT. Of these 854 events, there were 281 secular events in Year 1 and 573 in Year 2. This paper focuses on five specific categories: ‘tobacco use and cessation activities’, ‘farming’, ‘economics’, ‘city/county infrastructure’ and ‘wellness’. This protocol is a feasible yet time-intensive method of identifying events that may threaten the internal validity of a community-based RCT.